Apilimod activates the NLRP3 inflammasome through lysosome-mediated mitochondrial damage - Hou, Yingting; He, Hongbin; Ma, Ming; Zhou, Rongbin (Frontiers in Immunology, 2023)
NLRP3 is an important innate immune sensor that responses to various signals and forms the inflammasome complex, leading to IL-1β secretion and pyroptosis. Lysosomal damage has been implicated in NLRP3 inflammasome activation in response to crystals or particulates, but the mechanism remains unclear. We developed the small molecule library screening and found that apilimod, a lysosomal disruptor, is a selective and potent NLRP3 agonist. Apilimod promotes the NLRP3 inflammasome activation, IL-1β secretion, and pyroptosis. Mechanismically, while the activation of NLRP3 by apilimod is independent of potassium efflux and directly binding, apilimod triggers mitochondrial damage and lysosomal dysfunction. Furthermore, we found that apilimod induces TRPML1-dependent calcium flux in lysosomes, leading to mitochondrial damage and the NLRP3 inflammasome activation. Thus, our results revealed the pro-inflammasome activity of apilimod and the mechanism of calcium-dependent lysosome-mediated NLRP3 inflammasome activation.